In vitro evaluation of antimicrobial agents on Acanthamoeba sp. and evidence of a natural resilience to amphotericin B. Issue 3 (December 2017) - Taravaud, Alexandre; Loiseau, Philippe M.; Pomel, Sébastien
Abstract: The free-living amoeba (FLA) Acanthamoeba sp. is an opportunistic pathogen that can cause amoebic keratitis (AK) or granulomatous amoebic encephalitis (GAE). While current treatments of AK are long with some relapses, no consensus therapy has been developed for GAE remaining lethal in 90% of the cases. In this context, efficient antiacanthamoebal drugs have to be identified. In this work, 15 drugs used in the treatment of AK or GAE or in other parasitic diseases were evaluated for their in vitro activity on A. castellanii . Hexamidine, voriconazole and clotrimazole exhibited the highest activities with IC50 values at 0.05 μM, 0.40 μM and 0.80 μM, respectively, while rifampicin, metronidazole and cotrimoxazole were inactive. Among 15 drug associations evaluated, no synergistic effect was observed, and one antagonism was determined between hexamidine and chlorhexidine. Interestingly, amphotericin B was the only drug presenting an increase of IC50 as a function of treatment duration. The amoebae susceptibility to amphotericin B cultured in the presence of 250 μM of the drug was similar to the one of a naive control, revealing that no resistant strain could be selected. However, the amoebae susceptibility always returned to an initial level at each passage. This natural and non-acquired adaptation to amphotericin B, qualified as resilience, was observed in several strains of A. castellanii and A. polyphaga . Using a pharmacological approach with effectors of different cellular mechanisms or transports, and an ultrastructural analysis of amphotericin B-treated amoebae, the involvement of several mitochondria-dependent pathways as well as multidrug resistant transporters was determined in amphotericin B resilience. Based on the observations from this study, the relevance of using amphotericin B in GAE treatments may be reconsidered, while the use of some other drugs, such as rifampicin or cotrimoxazole, is not relative to intrinsic antiacanthamoebal activity. Graphical abstract: Image 1 Highlights: In vitro evaluation of 15 antimicrobial agents on Acanthamoeba castellanii . Best activity for hexamidine and inefficiency of rifampicin and cotrimoxazole. Antagonism of the combination chlorhexidine/hexamidine. Natural resilience of Acanthamoeba sp. for amphotericin B. Involvement of mitochondria-dependent pathways and MDR in amphotericin B resilience.